Knowledge Management and Pedagogical Innovativeness of Business Educators in Nigerian Universities - Chukwuemeke, Helen Edowaye; Owie, Tracy Yetunde (Journal of Pedagogy and Education Science, 2024)
The sole responsibility of business educators through pedagogical innovativeness is to equip their students with skills to make them self-sufficient; and to positively get involved in the nation’s well-being economically and otherwise. Considering this, hence a need to investigate the relationships between the three dimensions of knowledge management (KM) and pedagogical innovativeness (PI) of business educators in Nigerian Universities. The study adopted a correlational design and data were collected from 137 business educators in public universities in Nigeria. The authors employed a bivariate correlation linear regression and path analysis via the 5000 re-samples bootstrap method. The results revealed that knowledge management dimensions such as knowledge dissemination, and responsiveness to knowledge significantly predict pedagogical innovativeness while knowledge acquisition did not significantly predict pedagogical innovativeness. The results indicate that knowledge acquisition (KA) knowledge dissemination (KD) responsiveness to knowledge (RK) are the major pointers of pedagogical innovativeness. This result will help business education program stakeholders understand the important role knowledge management plays in all work processes.